Self-compacting nano silver paste and method for preparing interconnection layer for high power electronic devices
By using the three peaks of densely connected silver pulp, including micron -level silver particles and keys and silver nano particles, combined with multi -step heating and forming technology in situ, solving the reliability of the interconnection layer between high -temperature semiconductor devices and substrates. The interconnection layer of high thermal items and high heat stability is realized.
Patent Information
- Application Number
- CN202310063633.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2023-01-12
- Filing Date
- 2023-01-16
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-01-16
AI Technical Summary
The prior art is difficult to form a reliable interconnect layer between a high-temperature semiconductor device and a substrate. Especially at high temperatures, the thermal conductivity and melting point of traditional eutectic solder alloys and adhesives are insufficient, resulting in poor thermal stability and reliability problems. .
A three-peak densely connected silver pulp, which contains a 10-60 percentage percentage of micron-grade silver particles and 10-60 percentage bonding silver nano particles. Granules, remove the organic layer and antioxidant reducing agent, and finally sinter to form a interconnecting key layer.
A interconnection layer that forms high thermal conductivity, high fever stability and high reliability at high temperatures, solve the problem of failure of traditional materials at high temperature, and can form a dense key layer without external pressure.
Smart Images

Figure CN116580872B_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to U.S. Provisional Patent Application No. 63 / 300,043 filed on January 16, 2022, and U.S. Patent Application No. 18 / 154,033 filed on January 12, 2023, the disclosures of which are incorporated herein by reference. Technical Field
[0003] The present invention relates to self-compacting nano silver paste, and more particularly, to a self-compacting nano silver paste for connecting high power electronic devices. Background Art
[0004] Metal nanoparticles and their related inks / pastes have attracted wide interest in the printed electronics industry due to their unique properties of reduced particle size and increased surface area. Recently, there has been a method of directly using metal nanoparticle inks to print fine conductive patterns using an inkjet printing method. The ink used in this particular method must contain a high concentration of small nanoparticles that can be well dispersed in a solvent. For example, WO2009 / 111393 discloses a conductive ink comprising metal nanoparticles, a polymer dispersant, and a solvent, and further discloses that the content of the metal nanoparticles is about 10-60 weight percent of the ink.
[0005] In semiconductor packaging, die attach materials form electrical and / or thermal connections between semiconductor devices and their substrates / packages. Traditionally, lead-based solders are used to form such connections. Therefore, high-temperature lead-based solder alloys used for die attach are mature products in the semiconductor industry. However, lead-based materials can cause environmental and health issues. Environmental regulations in some regions require the use of lead-free solders for packaging, but lead-free solder alloys generally have lower melting temperatures and are susceptible to thermal fatigue and creep, resulting in long-term reliability issues. Although gold-based lead-free solder alloys have acceptable electrical and thermal properties, they are too expensive to use in most devices.
[0006] High-power semiconductor devices have higher breakdown voltages and lower switching losses, are capable of higher current densities, and operate at higher temperatures. These high-power devices use wide bandgap materials such as silicon carbide (SiC) and gallium nitride (GaN), both of which can operate at temperatures above 300°C. Since the use of these wide bandgap materials in high-power electronic devices increases the need for high heat dissipation, eutectic solder alloys or conventional die attach adhesives are not suitable as die attach materials due to their limited heat dissipation capabilities (thermal conductivity 30-60W / mK) and low melting points. Bonding wires using these conventional materials show low thermal stability and fail at high operating temperatures, so given the low thermal conductivity of the bonding layer material, it may be necessary to limit the power of high-power electronic devices.
[0007] Silver sintering provides a strong bond between the device and the substrate. During the sintering process, when the silver material is heated under optimal conditions (pressure, temperature and time), its form changes from powder to solid structure; compared with traditional solder materials, silver sintering can produce more reliable interconnect layers with significantly improved performance and life, and is more energy-efficient and produces less stress on semiconductor packaging.
[0008] Silver nanoparticles have been widely used in the interconnection of semiconductor devices and substrates due to their high melting temperature (961°C) and low sintering temperature. Through their excellent thermal and electrical conductivity, sintered silver can reduce the junction temperature (Tj) of the device to 100°C. When the particle size is reduced to the nanoscale, some special properties will be produced, such as lower melting temperature, higher surface energy and higher diffusion coefficient, which are significantly different from bulk silver.
[0009] One of the advantages of sintering nanosilver is that it can form a joint at a temperature comparable to that of lead-based solder; however, after sintering, the joint will not melt until the temperature exceeds the melting point of silver (961°C), and the nanosilver material also has the same excellent thermal, electrical and mechanical properties as silver blocks. The sintered nanosilver joint produced at a relatively low temperature can be used at high temperatures (over 500°C) where conventional solder joints fail.
[0010] Most uses of silver nanoparticles involve heat and pressure to achieve tight interconnections; pressure-assisted sintering methods require large capital investments in pressure-applying equipment and have very low manufacturing throughput, and the high pressures in the process can also cause chips to crack.
[0011] U.S. Patent No. 8,257,795 relates to a slurry whose metal particles are all nanoparticles, and pressure can be selected during the heating process. However, slurries made entirely of nanoparticles may be difficult to process. On the one hand, since nanoparticles tend to agglomerate, the slurry clogs the dispenser and affects the density of the final bonding layer, resulting in poor processability; in addition, metal nanoparticles are generally more expensive than particles in the micron range, increasing the cost of the slurry and the overall cost of the device using the slurry. Table 1 compares the performance of different traditional chip mounting materials.
[0012] Table 1: Performance of traditional die attach materials
[0013]
[0014] Therefore, there is a need in the art for improved die attach materials that can be used to form interconnect layers between high temperature semiconductor devices (eg, GaN or SiC based devices) and substrates. Summary of the invention
[0015] The present invention provides a self-densifying interconnection layer between a high-temperature semiconductor device and a substrate, wherein the high-temperature semiconductor device is selected from a GaN or SiC system device, and the interconnection layer includes a matrix having micron-sized silver particles, which accounts for about 10-60 weight percent, and the micron-sized silver particles have a particle size of about 0.1-15 microns; and the matrix of the micron-sized silver particles is chemically bonded with bonding particles, wherein the bonding particles are a core silver nanoparticle having smaller surface silver nanoparticles formed in situ, the surface silver nanoparticles are bonded to the core silver nanoparticles by chemical bonding, and are also bonded to the matrix having the micron-sized silver particles by chemical bonding, and the bonding particles have a core particle size of about 10 to about 100 nanometers, and the surface silver nanoparticles formed in situ have a particle size of about 3-9 nanometers.
[0016] In another aspect, the micron-sized silver particles are silver flakes or approximately spherical silver particles.
[0017] In another aspect, the substrate includes a layer of silver or gold having a thickness of about 0.1 to 0.3 microns.
[0018] In another aspect, the present invention provides a trimodal self-compacting interconnect silver paste, the paste comprising 10-60 weight percent of matrix silver particles, which are approximately micron-sized and have an average particle size of 0.1-15 microns, and the paste also comprises 10-60 weight percent of bonded silver nanoparticles, the bonded silver nanoparticles having core silver nanoparticles having a size of approximately 10-100 nanometers. The core silver nanoparticles have a polymer coating layer, which contains a dissolved or suspended silver salt precursor, the silver salt precursor can form surface silver nanoparticles bonded to the surface of the core silver nanoparticles, and the core silver nanoparticles have a particle size of approximately 10-100 nanometers, thereby forming composite silver nanoparticles having surface nanoparticles with a nanoparticle size of 3-9 nm. The paste also comprises 10-20 weight percent of at least one reducing solvent and 0.1-1 weight percent of an antioxidant reducing agent.
[0019] In another aspect, the slurry can include 30-50 weight percent matrix particles, 10-30 weight percent bonding particles, and 20-40 weight percent solvent.
[0020] In another aspect, the slurry can include 20-50 weight percent matrix particles, 30-40 weight percent bonding particles, and 20-30 weight percent solvent.
[0021] In another aspect, the slurry can include 30-40 weight percent matrix particles, 30-40 weight percent bonding particles, and 20-30 weight percent solvent.
[0022] In another aspect, the slurry can include 20-40 weight percent matrix particles, 30-50 weight percent bonding particles, and 10-20 weight percent solvent.
[0023] The trimodal interconnect silver paste may further include 0.1-1 weight percent of a non-conductive filler.
[0024] In the trimodal interconnect silver paste, the matrix silver particles of about micrometer scale can be silver flakes or nearly spherical silver particles.
[0025] The polymer coating layer of the trimodal interconnect silver paste may be polyvinyl pyrrolidone.
[0026] In the trimodal interconnect silver paste, the silver salt may be one or more of silver nitrate, silver chloride, silver acetate or silver sulfate.
[0027] In the trimodal interconnect silver paste, the at least one reducing solvent may be one or more of ethylene glycol, diethylene glycol, triethylene glycol or polyethylene glycol.
[0028] In the trimodal interconnect silver paste, the antioxidant reducing agent may be one or more of citric acid, caffeic acid, malic acid or dicarboxylic acid.
[0029] In the trimodal interconnect silver paste, the non-conductive filler may be one or more of SiC, SiO2, Al2O3, ZrO2, silicone microsphere particles, or other ceramic and polymer particles that are stable at sintering temperatures.
[0030] In another aspect, the present invention also provides a method for forming a self-densifying interconnect bonding layer between a high temperature semiconductor device and a substrate, wherein the high temperature semiconductor device is selected from a GaN or SiC-based device, which comprises placing the paste between the semiconductor device and the substrate and performing multi-step heating to heat the trimodal self-densifying interconnect silver paste to a first temperature between about 80 and 120° C. and for a period of time sufficient to in situ form surface silver nanoparticles on the surface of the core silver nanoparticles.
[0031] The slurry is heated to a second temperature between about 120 and 150° C. for a time sufficient to remove the organic layer on the matrix silver particles; the slurry is heated to a third temperature between about 150 and 200° C. for a time sufficient to remove the residual solvent; and finally, the slurry is heated to a fourth temperature between about 200 and 260° C. for a time sufficient to sinter the interconnect silver paste into an interconnect bonding layer.
[0032] In another aspect, the time sufficient to form surface silver nanoparticles in situ on the surface of the core silver nanoparticles is about 10 to about 30 minutes.
[0033] In another aspect, the time sufficient to remove the organic layer on the host silver particles is about 10 to about 30 minutes.
[0034] In another aspect, the time sufficient to sinter the interconnect silver paste to form the interconnect layer is about 30-90 minutes.
[0035] In another aspect, the interconnect bonding layer is formed without applying / adding pressure. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 A schematic diagram showing a packaged semiconductor device according to an embodiment of the present invention;
[0037] Figure 2A-2B Is applied to Figure 1 An enlarged schematic diagram of an interconnect structure and bonding particles in a packaged semiconductor device;
[0038] Figure 3 A graph showing the melting temperature of silver versus particle diameter;
[0039] Figure 4shows bonding according to an embodiment of the present invention;
[0040] Figure 5 showing formation of silver nanoparticles on core silver nanoparticles;
[0041] Figure 6 Showing the curing curve of the present invention; and
[0042] Figure 7 Showing the bonding of micron-sized silver particles to nano-sized particles. DETAILED DESCRIPTION
[0043] Overview:
[0044] Silver is a soft, ductile metal with high electrical and thermal conductivity. Silver nanoparticles, which are usually less than 100nm, do not oxidize in air, and are stable in water. Due to their unique physical and chemical properties, such as optical, electrical, thermal and biological properties, silver nanoparticles have recently been used in more and more fields, including medical, food, health care, consumer and industrial uses. As the size range of silver shifts to the nanoscale, the nanostructured silver has a higher specific surface energy and a higher surface-to-volume ratio, which increases its sensitivity to heat. In addition, the surface diffusion coefficient also increases with the decrease in particle size, indicating that the specific surface energy of nanoparticles is higher than that of microparticles or bulk materials; and the driving force for diffusion is inversely proportional to the size of the particles. A high driving force will lead to a lower sintering temperature for silver nanoparticles. Figure 3 The melting temperatures of silver particles of different sizes are shown in Figure 2, from which it can be seen that the melting temperature of particles with a diameter less than 10 nm is significantly reduced.
[0045] Figure 1 A semiconductor package 100 using the interconnect material of the present invention is schematically shown. The semiconductor package includes a device 10 and a substrate 20, the device 10 may be a GaN-based or SiC-based device, and the substrate 20 may be a ceramic material or other material capable of withstanding high temperatures. The device is connected to the substrate via an interconnect layer / chip attach layer 25, the substrate 20 may include an upper substrate metallization layer 55 and a lower substrate metallization layer 50, and the substrate 20 may be attached to a base plate 40 via an attach solder 30. The package may be bounded by an optional protective shell 60 filled with an optional encapsulation compound 70, and power terminals 65 may pass through the protective shell 60 to establish connections to a power source and other devices, and one or more wire bonds may connect the device 10 to the substrate metallization layer.
[0046] The interconnect / die attach layer 25 has Figure 2AThe metal layer of the microstructure shown, the interconnection layer 25 includes a matrix with micron-sized silver particles 26, the content of which is about 10-60 weight percent; wherein the particle size of the micron-sized silver particles 26 ranges from about 0.1 to 15 microns; bonding particles, used to chemically bond the matrix with the micron-sized silver particles 26, the bonding particles are surface silver nanoparticles 28 ( Figure 2B ), the surface silver nanoparticles 28 are chemically bonded to the surface of the core silver nanoparticles 27, and are also chemically bonded to the matrix having micron-sized silver particles 26, the bonded particles have a core silver nanoparticle 27 of about 10-100 nanometers, and the in-situ formed surface silver nanoparticles 28 have a particle size of about 3-9 nanometers.
[0047] Figure 2A-2B The interconnect layer 25 is made of a trimodal self-compacting metal interconnect paste. The term "trimodal" refers to the three metal particles used in the metal interconnect paste. It is worth noting that the terms "ink" and "paste" are sometimes interchangeable in this specification; generally, the viscosity of the paste is higher than that of the ink, and the ink tends to be more fluid. Those skilled in the art should understand these viscosity differences and how to produce a low viscosity ink from a high viscosity paste (usually through a larger percentage of solvent). In the trimodal slurry, micron-sized matrix metal particles and bonding particles can be used together, the bonding particles including metal nanoparticle cores with in-situ formed smaller metal particles attached to the surface, the slurry including 10-60 weight percent of micron-sized matrix silver particles with an average particle size of 0.1-15 microns, and the slurry also includes 10-60 weight percent of bonding silver nanoparticles with core silver nanoparticles of about 10-100 nanometers, the core silver nanoparticles having a polymer coating layer containing a silver salt precursor dissolved or suspended therein, the silver salt precursor can form surface silver nanoparticles attached to the surface of the core silver nanoparticles; wherein the core silver nanoparticles have a particle size of about 10-100 nanometers. When generated, the surface silver nanoparticles decomposed from the silver salt precursor have a particle size of 3-9 nanometers, which will be bonded to the surface of the core silver nanoparticles with a particle size of about 10-100 nanometers. Therefore, smaller surface nanoparticles with high surface energy will melt faster than core nanoparticles and micron-sized silver matrix particles, and can be used as a binder to bind the core particles and the matrix particles; the slurry also includes 10-20 weight percent of at least one reducing solvent and 0.1-1 weight percent of an antioxidant reducing agent.
[0048] The slurry of the present invention also includes other composition ranges, for example, the slurry may include 30-50 weight percent of matrix particles, 10-30 weight percent of bonding particles and 20-40 weight percent of solvent; or, the slurry may include 20-50 weight percent of matrix particles, 30-40 weight percent of bonding particles and 20-30 weight percent of solvent; in another aspect, the slurry may include 30-40 weight percent of matrix particles, 30-40 weight percent of bonding particles and 10-30 weight percent of solvent; in another aspect, the slurry may include 20-40 weight percent of matrix particles, 30-50 weight percent of bonding particles and 10-20 weight percent of solvent.
[0049] In one aspect, the interconnect / die attach layer 25 can be used to bond with a semiconductor chip / device 10 having a thin metal layer 21 on the lower surface; in one embodiment, the thin metal layer can be a thin silver or thin gold layer; similarly, a thin metal layer 21 can be present on the upper surface of the substrate 20; each thin metal layer has a thickness of about 0.1-0.3 microns. Using a thin metal layer can prevent the interconnect / die attach layer material 25 from failing at the bonding interface.
[0050] Material
[0051] Micron-sized silver particles
[0052] In the trimodal nano silver paste composition of the present invention, the micron-sized silver particles may preferably include at least one of silver flakes or approximately spherical silver particles, with a particle size of about 0.1-15 microns; the average particle size of the silver flakes is preferably 0.1-15 μm, because when the particle size is less than 0.1 μm, the bonding layer structure will have a high porosity and the thermal conductivity of the silver layer will be relatively reduced; when the particle size exceeds 15 μm, it is difficult to squeeze the silver flakes out of the dispenser. Micron-sized silver flakes can establish conductive paths at a high density within the bonding structure. In addition, compared with the paste using silver spherical particles, the paste using silver flakes provides better printability.
[0053] The slurry preferably contains about 10-60 mass percent silver flakes. When the content is less than 10 mass percent, the bonded structure shows high porosity, low thermal conductivity and poor shear strength performance; if the silver flake content exceeds 60 mass percent, the sintered structure will also show poor shear strength because the number of silver sintered bonds formed by the silver bonding particles is insufficient. On the other hand, the slurry may contain 20-50 mass percent silver flakes or 30-50 mass percent silver flakes, 20-40 mass% silver flakes or 30-40 mass% silver flakes.
[0054] Bonded Nanoparticles
[0055] Figure 5The bound nanoparticles 27 are shown before and after the smaller surface nanoparticles are bound to the core nanoparticles. The bound core nanoparticles 27 in the slurry are particles of about 10-100 nanometers in size, which are coated with a polymer 29; in one aspect, the polymer 29 can contain a silver salt, such as silver nitrate, silver chloride, silver acetate, or silver sulfate in polyvinyl pyrrolidone (PVP). Silver nanoparticles can be synthesized as described below:
[0056] Synthesis of silver nanoparticle mixture
[0057] 1. Dissolve polyvinyl pyrrolidone (PVP) in ethylene glycol (EG) or diethylene glycol (DEG) at a temperature of 90-160°C with mechanical stirring.
[0058] 2. Add an optional reducing agent to the above PVP solution. The choice of reducing agent and its concentration depend on the selected metal salt.
[0059] 3. Dissolve the metal salt in deionized water or ethylene glycol solution.
[0060] 4. Add the silver salt solution to the PVP solution at a controlled rate.
[0061] 5. After the reaction is completed, the silver nanoparticles are separated from the solution by centrifugation.
[0062] 6. Purify the nanoparticles by washing with acetone / alcohol solvent and separating by centrifugation.
[0063] Alternatively, a catalytic reduction modifier PVP can be used to form a silver nanoparticle mixture. PVP is used as a protective agent, and its dosage and molecular weight can effectively control the morphology, dispersibility and size of the silver particles. The molecular weight of PVP can be 10,000 to 100,000 Mw. When the molecular weight is lower than 10,000, which is a low molecular weight (Mw) and a low glass transition temperature (Tg), PVP cannot effectively control the metal salt because the size distribution of nanosilver covers a wider range during the reduction process; and when Mw is greater than 100,000, PVP is likely to form a linear shape, causing nanosilver to tend to assemble into a linear structure. Therefore, a molecular weight of 40,000 will be selected as the molecular weight of PVP to well control the size of nanosilver, as shown schematically below:
[0064]
[0065] The mass ratio between the silver salt and the PVP may be selected to be 1:3 to 1:7; it also includes 1:4 to 1:6, 1:5 to 1:7 and 1:4 to 1:5.
[0066] When the mass ratio is lower than 1:3, the average particle size of the nanosilver is too large and is prone to aggregation; when it exceeds 1:7, the nanosilver modified layer will be too thick and cannot be washed off.
[0067] like Figure 5 As shown, the average size of the formed silver nanoparticles 28 is 10-100 nm. The silver nanoparticles 28 with the PVP coating layer 29 are washed with acetone / alcohol solvent and separated by centrifugation several times. The PVP coating layer synthesized by the above steps contains Ag ions for in-situ silver nanoparticle formation.
[0068] Reducing solvent
[0069] An optional solvent can be used together with the silver particle mixture. The solvent can use any known reducing agent solvent as the solvent. The solvent is preferably an ethylene glycol-based solvent. Ethylene glycol-based solvents include ethylene glycol, diethylene glycol, triethylene glycol and polyethylene glycol, propylene glycol, dipropylene glycol, etc. The trimodal nano silver paste composition of the present invention can optionally include at least one reducing solvent, which can be one or a combination of the above-mentioned solvents, and the amount of the reducing solvent is preferably about 10-30 mass percent, including 10-20 mass percent and 20-30 mass percent.
[0070] The solvent used as a reducing agent not only converts silver ions into silver nanoparticles bound to the surface of the core silver nanoparticles, but also removes any oxide layer on the substrate to be bonded, and provides a strong connection between the bonding wire layer and the substrate or between the bonding wire and the chip; in particular, the reducing ability of the reducing solvent can be further increased with the increase in temperature during the curing process, so the curing time can be extended during the nucleation of the silver nanoparticles to obtain the maximum amount of silver nanoparticles formed in situ, and the curing time can be extended at an appropriate temperature to further remove any oxide layer from the substrate; in addition, the reducing solvent can also remove any surface coating of the silver flakes in the slurry, such as stearic acid or oxides, otherwise, such coatings on the silver flakes will reduce the thermal conductivity of the bonding wire layer. Therefore, the cured film is dense and has high conductivity and high adhesion to the substrate and the chip.
[0071] Another consideration in selecting a reducing solvent is the boiling point. Since the boiling point of the solvent should not exceed 260°C when the silver paste is sintered at a temperature as high as 260°C, and the formation of in-situ silver nanoparticles occurs at about 80-120°C, a reducing solvent with a boiling point exceeding 120°C should be selected; therefore, the boiling point of the solvent is selected to be about 120 to 260°C, more preferably 150 to 260°C. In order to further extend the time that the solvent remains in the slurry to ensure sufficient time to form in-situ particles and remove the oxide layer, the solvent can be a combination of two different solvents, each having a different boiling point, so that the solvent can evaporate in a step-by-step manner, which will also help to produce a more compact bonding structure.
[0072] The amount of the solvent is preferably 10 to 20 parts by mass based on silver. If it is less than 10 parts by mass, the viscosity increases and the workability decreases; if it exceeds 20 parts by mass, the viscosity decreases and the paste becomes too thin to print.
[0073] Antioxidant
[0074] Antioxidant-reducing agent can be added to the composition of trimodal nano silver paste. In the present invention, antioxidant-reducing agent refers to those materials with fluxing activity, which are used to remove the oxide coating of substrate and chip, the stearic acid coating on the surface of micron-sized silver particles, and the residual PVP coating on the silver nanoparticles, and in addition, it can prevent the substrate surface from being oxidized again during high temperature curing. A clean substrate surface contributes to the mechanical strength at the bonding interface, avoids crack formation, and a clean micron-sized silver particle surface also contributes to improving thermal conductivity. Antioxidant-reducing agent includes citric acid, caffeic acid, malic acid and dicarboxylic acids (such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, etc.). If the amount used is less than 0.1%, there is no reducing effect. If the amount of the antioxidant reducing agent used exceeds 1 mass percent, the thermal conductivity of the bond will be reduced. In addition, the decomposition temperature of the antioxidant reducing agent should not exceed 200°C so that the reducing agent can be removed within the temperature range of 150-200°C before the sintering process of silver begins, because if the reducing agent is not removed before sintering, it may have a negative impact on the bonding and lead to a decrease in shear strength.
[0075] Optional non-conductive filler
[0076] The trimodal nano silver paste composition of the present invention may optionally include a non-conductive filler. The non-conductive filler may be selected from one or more of SiC, SiO2, TiO2, Al2O3, or other ceramic and polymer particles that are stable at sintering temperatures, such as silicone microspheres. The purpose of adding a non-conductive filler to the slurry is to densify the slurry structure and avoid void aggregation that may have a negative impact on shear strength and thermal conductivity during particle generation. The addition of non-conductive particles can improve the high temperature stability and high hydrothermal stability of sintered nano silver bonding, and can also limit the increase in thermal resistance during thermal cycles at low and high temperatures, and the shear strength increases with the increase in the proportion of SiC in the trimodal nano silver paste. The size of the non-conductive filler particles is preferably between about 50-1000nm. When there is a non-conductive filler in the silver paste, its content is preferably 0.1 to 1 mass percent relative to 100 mass parts of the trimodal nano silver paste component.
[0077] Step-by-step curing densification method
[0078] In another aspect, the present invention provides a multi-step curing method that can make the metal paste self-densifying and form a strong bond at low temperature without applying pressure during the bonding process. The multi-step curing method includes (S1) in-situ forming silver nanoparticles, (S2) removing the oxide layer of the micron-sized silver particles and combining the silver nanoparticles, (S3) removing the residual antioxidant reducing agent, and (S4) sintering the silver nanoparticles. Figure 6 The multi-step curing method of the present invention is schematically shown. Therefore, the multi-step curing method of the trimodal nanosilver paste provides a dense bonding structure between the chip and the substrate without applying external pressure during bonding.
[0079] In the first step, silver nanoparticles are generated in situ from metal salts in a polymer layer surrounding core nanoparticles, and the generation temperature is about 80-120°C and the generation time is about 10-30 minutes; the second step is to remove the oxide layer from the organic layer on the substrate and the micron-sized silver flakes / spherical silver particles, and the temperature of this step is about 120-150°C and the duration is about 10-30 minutes; the third step is to remove the residual antioxidant reducing agent, and the operating temperature is about 150-200°C and the duration is about 10-30 minutes; the fourth step is to sinter the silver nanoparticles, and the sintering temperature is about between 200-260°C and the duration is about 30-90 minutes. Figure 7 Schematically shown in FIG. 5 are particles in a solvent and upon removal of the solvent, the particles are combined with micron-sized silver particles.
[0080] Using the trimodal nano silver paste composition and multi-step curing method of the present invention, in-situ silver nanoparticles are formed around core nanoparticles of bonded particles from a polymer / PVP coating containing a silver salt, such as Figure 5 As shown, in the presence of an ethylene glycol-based solvent that also acts as a reducing agent, a certain amount of small-sized silver nanoparticles (3-9 nm) are generated on the surface of the bonded nanoparticles to form a shell of smaller nanoparticles on the core nanoparticles (larger). Importantly, the small nanoparticles 28 are chemically bonded to the matrix silver nanoparticles 27 before sintering into larger micron-sized silver flakes / spherical silver particles.
[0081] The composition can be optimized to ensure a high packing density. Since the solvent material is slowly removed during the multi-step curing and sintering process, the voids created by the evaporation / decomposition of the solvent / additives are filled with the silver nanoparticles 27; that is, due to its high packing density and multi-step curing method, the structure is self-compacting; due to the self-compacting structure formed when the solvent and additives are removed in steps 2 and 3, when the trimodal nanosilver paste is sintered in the final step of the curing / sintering method, rarely voids are formed; and the in-situ formed silver nanoparticles are sintered at a low temperature (about 112°C) and act as a metal adhesive on the silver nanoparticles, which can act as strong bonding particles in larger micron-sized particles. The final bonding structure of the three types of silver particles mentioned above is as follows: Figure 2A shown.
[0082] Example 1: Synthesis of Silver Nanoparticles with PVP Coating
[0083] 36.4 g of polyvinyl pyrrolidone (PVP) (Mw of 50,000) was dissolved in 75 mL of ethylene glycol under magnetic stirring and heated to 120°C, and 5.8 g of silver nitrate was dissolved in 25 mL of ethylene glycol. The silver nitrate solution was then added to the PVP solution, stirred for reaction for 1 hour, and then cooled to room temperature. After the reaction was completed, the mixture was centrifuged at 10,000 rpm and washed with ethanol and acetone. The undried purified silver nanoparticles were stored in ethanol for subsequent ink / paste preparation.
[0084] Example 2: Formula of Sanfeng Nano Silver Paste
[0085] The following table lists several composition formulations according to the present invention and comparative compositions. As shown in the following table, the composition according to the present invention exhibits significantly higher thermal conductivity and higher shear strength before and after thermal aging. In addition, compared with the existing composition (comparative composition), the porosity and resistivity of the composition of the present invention are lower.
[0086] Table 2: Examples of specific formulations:
[0087]
[0088]
[0089] *Step Curing Profile: The above step curing densification method.
[0090] Controlled curing method:
[0091] P2: Direct curing at 260°C
[0092] P3: Reach equilibrium at 30℃, raise the temperature to 130℃ at a rate of 10℃ / min, maintain isothermal temperature for 30 minutes, and then
[0093] The temperature was raised to 260°C at a rate of minutes and kept at this temperature for 60 minutes.
[0094] Industrial Applicability
[0095] By combining the trimodal nanosilver paste of the present invention with a multi-step curing densification / bonding method, it can be used for pressureless sintering as well as pressure sintering, and the bonding exhibits excellent adhesion between the semiconductor device and the substrate. The bonding also exhibits excellent shear strength and has high thermal conductivity and high thermal stability during high temperature aging tests.
[0096] As used herein and not otherwise defined, the terms "substantial," "substantially," "approximately," and "approximately" are used to describe and illustrate minor variations. When used with an event or circumstance, the terms may include instances where the event or circumstance occurred exactly as well as instances where the event or circumstance nearly occurred. For example, when used with a numerical value, these terms may include a range of variation of less than or equal to ±10% of the numerical value, such as less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%.
[0097] The above description is for the purpose of illustrating and describing the present invention. It is not intended to be exhaustive or to limit the present invention to the precise form disclosed. Many modifications and variations will be apparent to those skilled in the art. The above embodiments are selected and described in order to best explain the principles of the present invention and its practical application, so that other technical personnel in the art can understand the various embodiments of the present invention and various modifications suitable for the intended specific use.
Claims
1. A method for forming a trimodal self-densifying interconnect layer between a high temperature semiconductor device selected from GaN or SiC system and a substrate, characterized in that: include: A trimodal self-densifying interconnect silver paste is placed between a high-temperature semiconductor device selected from a GaN or SiC system and a substrate, wherein the trimodal self-densifying interconnect silver paste comprises: 10 to 60 weight percent of micrometer-sized matrix silver particles having an average particle size of 0.1 to 15 micrometers; 10 to 60 weight percent of bonded silver nanoparticles, the bonded silver nanoparticles having a core silver nanoparticle of 10 to 100 nanometers, the core silver nanoparticles having a polymer coating comprising a dissolved or suspended silver salt precursor that forms surface silver nanoparticles bonded to the surface of the core silver nanoparticles; and 10 to 20 weight percent of at least one reducing solvent; heating the trimodal self-densifying interconnected silver paste to a first temperature between 80 and 120° C. for a time sufficient to form surface silver nanoparticles in situ on the surface of the core silver nanoparticles; heating the trimodal self-densifying interconnect silver paste to a second temperature between 120 and 150° C. for a time sufficient to remove an organic layer on the matrix silver particles; heating the trimodal self-densifying interconnect silver paste to a third temperature between 150 and 200° C. for a time sufficient to remove residual solvent; and The trimodal self-densifying interconnect silver paste is heated to a fourth temperature between 200 and 260° C. for a time sufficient to sinter the silver interconnect paste into an interconnect bond.
2. The method according to claim 1, wherein the time sufficient to form surface silver nanoparticles in situ on the surface of the core silver nanoparticles is 10 to 30 minutes.
3. The method according to claim 1, wherein the time sufficient to remove the organic layer on the host silver particles is 10 to 30 minutes.
4. The method of claim 1, wherein the time sufficient to sinter the silver interconnect paste to form interconnects is 30-90 minutes. The method of claim 1 , wherein the interconnect bond is formed without applying / adding pressure. 6 . The method according to claim 1 , wherein the trimodal self-densifying interconnect silver paste further comprises 0.1-1 weight percent of a non-conductive filler.
7. The method of claim 1, wherein the polymer coating is polyvinyl pyrrolidone.
8. The method according to claim 1, wherein the silver salt precursor is selected from one or more of silver nitrate, silver chloride, silver acetate or silver sulfate.
9. The method of claim 1, wherein the at least one reducing solvent is selected from one or more of ethylene glycol, diethylene glycol, triethylene glycol or polyethylene glycol.
10. The method according to claim 1, wherein the trimodal self-densifying interconnect silver paste further comprises 0.1 to 1 weight percent of an antioxidant reducing agent.
11. The method according to claim 6, wherein the non-conductive filler is selected from one or more of SiC, SiO2 or Al2O3, ZrO2, silicone microsphere particles or other ceramic and polymer particles that are stable at sintering temperature.
12. The method according to claim 1, wherein the micron-sized matrix silver particles are selected from silver flakes or approximately spherical silver particles.
13. The method according to claim 10, wherein the antioxidant reducing agent is selected from one or more of citric acid, caffeic acid, malic acid or dicarboxylic acid.
14. A trimodal self-densifying interconnect layer formed between a high temperature semiconductor device selected from GaN or SiC system and a substrate according to the method of claim 1, characterized in that: include: A matrix having micron-sized silver particles, the content of which accounts for 10-60 weight percent, and the particle size of the micron-sized silver particles ranges from 0.1 to 15 microns; and The bonded particles can be fused with the matrix having micron-sized silver particles, which are core silver nanoparticles having smaller surface silver nanoparticles formed in situ on the surface, wherein the surface silver nanoparticles formed in situ are bonded to the surface of the core silver nanoparticles by chemical bonding and are also bonded to the matrix having micron-sized silver particles by chemical bonding, wherein the bonded particles have a core particle size of 10 to 100 nanometers, and the surface silver nanoparticles formed in situ have a particle size of 3 to 9 nanometers.
15. The trimodal self-densifying interconnect layer according to claim 14, wherein the micron-sized silver particles are selected from silver flakes or approximately spherical silver particles.
16. The trimodal self-densifying interconnect layer according to claim 14, wherein the substrate comprises a silver or gold layer having a thickness of 0.1 to 0.3 micrometers.
Citation Information
Patent Citations
Nanoscale metal paste for interconnect and method of use
US8257795B2
Additives and modifiers for solvent- and water-based metallic conductive inks
WO2009111393A2
Copper / silver core-shell nano particle low-temperature sintering composite welding paste and preparation method thereof
CN105127609A
Silver particle synthesizing method, silver particles, conductive paste producing method, and conductive paste
US20170144220A1